The cooperation of multiple actors within process models: an automated planning approach. Issue 4 (2nd October 2018) - Heinrich, Bernd; Schiller, Alexander; Schön, Dominik
ABSTRACT: In many business processes, multiple actors such as different employees, departments or companies are involved. These actors need to work together and form appropriate partnerships in parts of these processes to achieve their individual goals. Hence, from a Business Process Management perspective, the actors need to cooperate. We present a conceptual foundation for multi-actor process models, which enables the consideration of individual starting points and goals as well as partnerships. Further, we incorporate the cooperation of actors in the control flow of process models by constructing explicit actions determining where in the process to form and disband partnerships. We pursue an automated planning approach due to the complexity of the required cooperation. The constructed multi-actor process models are proven to be correct and complete. We demonstrate the feasibility of our approach by an application in several real-world scenarios and its effectiveness through the assessment of a practitioner.